Neglected tropical diseases and conditions of the nervous system - Cavalheiro, Esper A.; Kristensson, Krister; Patel, Nilesh B.; Bentivoglio, Marina (Springer New York, 2014)
A number of diseases and conditions that occur primarily in remote rural or poor urban areas of low-income countries have traditionally been neglected by the neuroscience research community. These diseases and conditions affect the nervous system directly (sometimes with lethal consequences) and/or are associated with severe neurological sequels such as epilepsy, cognitive deficits, and sleep disruption. Several diseases also have the effect of promoting poverty by leaving sufferers unable to lead economically productive lives due to cognitive and behavioral disturbances or severe stigmatization. The pathogenesis of neural dysfunction in the diseases addressed in this book and their sequels remains unclear. Neuroscience of Neglected Diseases and Conditions makes available much needed information about how these diseases affect the human nervous system as well as to promote interest in further research. Further research into neglected diseases and conditions will uncover information that sheds light on more general topics of interest to the neuroscience research community.